Aplicación de un modelo didáctico de enseñanza de la traducción - Olvera Lobo, M.; Castro, M.; Quero, E.; Muñoz, E.; Muñoz, R.; Murillo, M.; Robinson, B.; Senso, J.; Vargas, B. (Eslavística Complutense, 2004)
This article describes aula.int: a virtual translation classroom developed by a group of lecturers from the Faculty of Translation and Interpreting at the University of Granada, Spain. The objective of aula.int is to complement teaching in a number of subjects from the University's first degree program in Translation and Interpreting by offering a student-centred learning experience. Cooperation within the virtual classroom allows students to consolidate their learning in an environment designed to simulate that of a translation agency.
Keywords: Translation teaching; Virtual classroom; Teaching; Learning